Birthweight, HIV exposure and infant feeding as predictors of malnutrition in Botswanan infants - Chalashika, P.; Essex, C.; Mellor, D.; Swift, J.A.; Langley-Evans, S.C. (Wiley, 2017)
Background: A better understanding of the nutritional status of infants who are HIV-Exposed-Uninfected (HEU) and HIV-Unexposed-Uninfected (HUU) during their first 1000 days is a key to improving population health, particularly in sub-Saharan Africa. Methods: A cross-sectional study compared nutritional status, feeding practices and determinants of nutritional status of HEU and HUU infants residing in representative selected districts in Botswana during their first 1000 days of life. Four hundred and thirteen infants (37.3% HIV16 exposed), aged 6-24 months attending routine child health clinics were recruited. Anthropometric, 24-hour dietary intake and socio-demographic data was collected. Anthropometric z-scores were calculated using 2006 WHO growth standards. Modelling of the determinants of malnutrition was undertaken using logistic regression. Results: Overall, prevalence of stunting, wasting and underweight were 10.4%, 11.9% and 10.2% respectively. HEU infants were more likely to be underweight (15.6% vs. 6.9%), (p<0.01) and stunted (15.6% vs. 7.3%), (p<0.05) but not wasted (p= 0.14) than HUU infants. HEU infants tended to be formula fed (89.4%) whereas HUU infants tended to breastfeed (89.6%) for the first six months (p<0.001). Significant predictors of nutritional status were HIV exposure, birthweight, birth length, Apgar score and mother/caregiver’s education with little influence of socioeconomic status. Conclusions: HEU infants aged 6-24 months had worse nutritional status compared to HUU infants. Low birthweight was the main predictor of undernutrition in this population. Optimisation of infants’ nutritional status should focus on improving birthweight. In addition, specific interventions should target HEU infants in order to eliminate growth disparity between HEU and HUU infants.